2020
DOI: 10.3390/medicina56020057
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of KLF17 Predicts a Favorable Prognosis in Patients with Oral Squamous Cell Carcinoma: A Retrospective Study

Abstract: Background and Objectives: Patients with oral squamous cell carcinoma (OSCC), a common malignancy in Asian countries, have a poor prognosis. We investigated the role of Krüppel-like factor 17 (KLF17) and its prognostic significance in OSCC. Materials and Methods: KLF17 expression was measured by immunohistochemical staining of specimens from 283 patients with OSCC. We analyzed correlations between KLF17 expression and clinicopathologic features and between KLF17 expression and overall survival. The prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The clinicopathological features collected included gender, age, risk factors, histological type, and TNM stage (tumor (T), nodes (N), and metastases (M) satge) from the established database. The pathological diagnoses had been previously confirmed by two pathologists [ 20 , 21 ]. Those patients with missing clinical data or tissue loss during the IHC staining procedure were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…The clinicopathological features collected included gender, age, risk factors, histological type, and TNM stage (tumor (T), nodes (N), and metastases (M) satge) from the established database. The pathological diagnoses had been previously confirmed by two pathologists [ 20 , 21 ]. Those patients with missing clinical data or tissue loss during the IHC staining procedure were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, there is much evidence demonstrating that expression of these transcription factors is altered in a number of human cancers, where they can act as tumour suppressor or oncogenes, in a context-dependent way [8,9]. Various recent studies have also identified members of KLF family as novel prognostic biomarkers in cancer [10][11][12]. With respect to ovarian cancer, only sporadic data are available.…”
Section: Introductionmentioning
confidence: 99%
“…The clinicopathological features collected from the established database included risk factors, histological type, differentiation, and TNM stage. The histological diagnoses had previously been confirmed by two pathologists (20,21). Those patients with missing data or tissue loss during the immunohistochemical (IHC) staining procedure were excluded from this study to reduce the bias from missing data.…”
Section: Methodsmentioning
confidence: 99%